2014
DOI: 10.1051/eas/1567039
|View full text |Cite
|
Sign up to set email alerts
|

GALAH survey: chemically tagging the thick disk

Abstract: Abstract. The GALAH survey targets one million stars in the southern hemisphere down to a limiting magnitude of V = 14 at the AngloAustralian Telescope. The project aims to measure up to 30 elemental abundances and radial velocities (≈ 1 km s −1 accuracy) for each star at a resolution of R = 28, 000. These elements fall into 8 independent groups (e.g. α, Fe peak, r-process). For all stars, Gaia will provide distances to 1% and transverse velocities to 1 km s −1 or better, giving us a 14D set of parameters for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…The top panel of Fig. 1 shows the previous calibration, the middle panel shows the new calibration and the bottom panel shows the 2 The GeTCal code and the T eff and [Fe/H] calibrations are available at http://www.astro.up.pt/exoearths/tools.html. [19].…”
Section: Getcalmentioning
confidence: 99%
See 1 more Smart Citation
“…The top panel of Fig. 1 shows the previous calibration, the middle panel shows the new calibration and the bottom panel shows the 2 The GeTCal code and the T eff and [Fe/H] calibrations are available at http://www.astro.up.pt/exoearths/tools.html. [19].…”
Section: Getcalmentioning
confidence: 99%
“…The volume of data being produced by large-survey observational programs [2,4] requires the existence of quick methods to obtain stellar parameters for a diverse range of stellar spectral types.…”
Section: Introductionmentioning
confidence: 99%
“…Large-survey observational programs such as GES (Gilmore et al 2012), GALAH (Bland-Hawthorn et al 2014), and RAVE (Steinmetz et al 2006) are quickly becoming the new paradigm of stellar observations and characterization. Given the volume of data involved, the success of these programs relies on the existence of methods that rapidly ascertain stellar parameters for a diverse range of stellar spectral types.…”
Section: Introductionmentioning
confidence: 99%
“…This information is crucial as studies (e.g., Escala & Larson 2008;Kruijssen 2012) have shown that the maximum aggregate size that stars form might depend on the star formation rate and the gas mass in the past. Since most of the clusters are soon disrupted (Lada & Lada 2003), constraining the past cluster mass function through chemical tagging may be the best option (Bland-Hawthorn et al 2014;Ting et al 2015b).…”
Section: Introductionmentioning
confidence: 99%